آليات الاتساق النحوى في سورة فاطر ودورها في الترابط النصي - سعداني، سليم; بن عبد الله، راضية; عيساوي، وجدة (University of Eloued جامعة الوادي, 2024)
قمنا في هذا البحث بدراسة موضوع "آليات الاتساق النحوي في سورة فاطر ودورها في الترابط النصي"، وقد انطلقنا من إشكالية مفادها: ما هو دور آليات الاتساق النحوي في تحقيق التماسك النصي في سورة فاطر؟ وكيف تجلى ذلك؟ وما مفهوم الاتساق؟ وما المقصود بالاتساق النحوي؟ ما هي آلياته وما دور كل منها؟ وذلك بهدف الوقوف على أبرز الأدوات التي أسهمت في اتساق السورة، وعلى هذا قسمنا البحث إلى: مقدمة وفصلين، الأول نظري والثاني كان نظريا وتطبيقيا، وخاتمة. تناولنا في الفصل الأول مصطلحاتٍ ومفاهيمَ عامة حول لسانيات النص، أمّا الفصل الثاني فتطرقنا فيه لمفهوم الاتساق وآلياته وتجليها في سورة فاطر، وكيف أسهمت في اتساق السورة وترابط مقاطعها، وذلك بتطبيق المنهج الوصفي والإجراء التحليلي، وأنهينا البحث بخاتمة تضمنت أهم النتائج المُتوصَل إليها أثناء دراستنا لهذا البحث. Abstract In this research, we studied the topic "Mechanisms of Syntactic Coherence in Surah Fatir and its Role in Textual Cohesion". We started from the problem of: What is the role of syntactic coherence mechanisms in achieving textual cohesion in Surah Fatir? How does this manifest? What is the concept of coherence? What is meant by syntactic coherence? What are its mechanisms and roles of each? The aim was to identify the key tools that contributed to the coherence of the Surah. Therefore, we divided the research into: an introduction, two chapters - the first theoretical and the second both theoretical and applied, and a conclusion. In the first chapter, we addressed general terminology and concepts related to discourse linguistics, while in the second chapter, we discussed the concept of coherence, its mechanisms, and manifestation in Surah Fatir, and how they contributed to the coherence and connection of its segments through the application of a descriptive-analytical approach. We concluded the research with a summary of the most important findings reached during our study of this research.
415/ 005
Keywords: الاتساق، آليات، النص، الخطاب، الجملة، نحو النص، سورة فاطر. Coherence; Mechanisms; Text; Discourse; Sentence; Textual Syntax; Surah Fatir